Pengaruh Live Streaming Tiktok dan Online Cutomer Review terhadap Minat Beli Produk Camille Beauty - Anggraeni, Desi (IPM2KPE, 2024)
This study aims to analyze the influence of TikTok Live Streaming and online customer reviews on consumer purchase intention towards Camille Beauty products. A quantitative approach was used in this study involving 170 respondents who had watched Camille Beauty's TikTok Live and read its online reviews. The sample was taken using non-probability sampling with a purposive sampling technique. Data were collected through questionnaires and analyzed using SEM (Structural Equation Modeling) based on PLS (Partial Least Squares). The results showed that Live Streaming significantly influenced purchase intention, with access to information as the most influential indicator, while streamers or presenters had a relatively low influence. Online Customer Reviews also significantly influenced purchase intention, with review quality as the best indicator and the quality of explanation regarding the advantages and disadvantages of the product as the lowest indicator. Overall, the variables Live Streaming and Online Customer Reviews have a simultaneous effect on consumer purchase intention. Keywords: Live Streaming, Online Customer Review, Purchase